Characteristics of granitic rock from western and eastern of the Bentong Raub suture, peninsular Malaysia - Ghani, A.A. (2008)
A first order difference between the Western and Eastern Belt Granites of Peninsular Malaysia is the S type nature of the former and the expanded compositional range of the Eastern Belt (SiO2: 50 to 78% SiO2) compared to that of the Western Belt (SiO2 > 65%). Magmatic evolution of the Western Belt Granites was controlled by K-feldspar, plagioclase and biotite whereas in the Eastern Belt granite, hornblende, K feldspar, plagioclase and biotite was the important mineral assemblage in the magmatic evolution. Zircon inheritance ages for of the eastern Belt Granite give a range from 900 to 1400 Ma younger than the Western Belt Granite dated between 1500 to 1700 Ma.